Next-Generation Smart Inverters: Bridging AI, Cybersecurity, and Policy Gaps for Sustainable Energy Transition - Hilmy Awad; Ehab H. E. Bayoumi (Technologies)
Smart inverters are pivotal in modern renewable energy systems, enabling efficient grid integration, stability, and advanced control of distributed energy resources. While existing literature addresses their technical functionalities, significant research gaps persist in areas such as interoperability, cybersecurity, standardization, and the integration of artificial intelligence for adaptive control. This article provides a comprehensive review of smart inverter technologies, emphasizing their role in renewable energy applications, advanced control strategies, and unresolved challenges. By systematically analyzing recent advancements and case studies, the paper identifies critical limitations in current practices, including economic barriers, regulatory misalignments, and fault tolerance under dynamic grid conditions. The review contributes to the field by synthesizing dispersed knowledge, highlighting under-researched areas, and proposing actionable pathways for future innovation. The main findings reveal the transformative potential of AI-driven grid-forming inverters for enhancing grid stability and resilience. However, their widespread adoption is hindered by the absence of harmonized standards and misaligned policy frameworks. Consequently, this review underscores the urgent need for policymakers to develop and implement supportive regulatory structures that facilitate the deployment of AI-enabled smart inverters and establish unified standards to ensure interoperability and cybersecurity. This work serves as a foundational reference for researchers and policymakers aiming to address technical and systemic bottlenecks in smart inverter deployment.